United Republic of Tanzania : Poverty Reduction Strategy Paper; Annual Implementation Report 2006/07. (IMF Staff Country Reports; Country Report ;, 2008)
The MKUKUTA Annual Implementation Report (MAIR) is one of the outputs of the Tanzanian government's monitoring system. The objective of this report is to contribute to all government reporting systems, which include output reporting by Ministries, Departments and Agencies, Local Government Authority, and non-state actors implementing MKUKUTA activities. It is based on analysis of progress at the goal level, and provides an overview of performance, challenges, lessons learned, and next steps within each MKUKUTA cluster. It also includes progress on other processes and reforms and how these have contributed to achievements of MKUKUTA outcomes.